Beyond the Math: Case Studies of Black Forest Landowners in Georgia, United States. (16th March 2023) - Hitchner, Sarah; Goyke, Noah; Thomas, Marc; Schelhas, John; Dwivedi, Puneet
ABSTRACT: Economic analyses of forest management options can help landowners make informed decisions. However, landowners make decisions in complex and nuanced ways that transcend economics. The history and legal status of their land, their emotional connections to it, their access to knowledge and capital, and their broader objectives are vital elements in their decision-making processes. We present case studies of four Black landowners in Georgia through a combination of economic analyses that compare their current revenue with potential increased revenue through active forest management and qualitative interviews that provide context for past management decisions and insights into why active forest management may – or may – not prove to be their ultimate goal. Together these two types of analysis present a range of goals and management options that consider both economic and non-economic valuations of forested lands, which can inform extension and outreach strategies for increasing engagement of Black landowners in sustainable forestry.